The structuring of the metaverse through the info-noospheric optics - Aleksandr A. Yefanov (RUDN Journal of Studies in Literature and Journalism)
The structuring of the virtual universe is considered in the context of the formation of the global information space as the separation of a part of the noosphere. The theoretical and methodological basis of the study is based on the noospheric theory of V.I. Vernadsky and the wave concept of civilization of E. Toffler. A set of methods is used: structural analysis; systematization; modeling; case study. Based on the results of the study, it is concluded that the metaverse is an info-noospheric formation, which, as a result of seamless simulation, acquires a spatial form, implements social practices in its disposition and, on this basis, builds the social structure of the modern neo-information society. The metaverse is becoming an increasingly expanding subform of social space (within its generic category), harmoniously integrating the socio-cultural and media levels, causing their significant syncretism. The metaverse is considered as the highest level of implementation of transmedia extensions, ensuring subordination to media processes both in online and offline modes. The metaverse has a complex structure, accumulating differentiated platforms that are united into ecosystems (digital), determining platform capitalism, as holders of which is the digital elite.